Synthesis, characterization and antibacterial activity of colloidal silver nanoparticles encapsulated in low generation poly(amido)amine dendrimers - Hamidon, Nurul Hanisah (2015)
Poly(amidoamine) (PAMAM) dendrimers of low generations 0.5, 1.0, 1.5, and 2.0 were synthesized in methanol via the divergent synthesis method, which includes alternating reiteration of Michael addition followed by ester amidation starting from ethylenediamine and methyl acrylate. PAMAM dendrimer encapsulated with silver nanoparticles were prepared by in situ reduction of AgNO3 solution with NaBH4 in the presence of PAMAM dendrimers. This procedure resulted in stable yellowish colloidal solutions which turn into dark brown colloid and precipitated as deep black solid silver(I) oxide, Ag2O upon exposure to light. Verification of the PAMAM structures was done using fourier transform infrared (FT-IR) spectroscopy, and 1H nuclear magnetic resonance (NMR) spectroscopy. The results of 1H NMR spectra of synthesized PAMAM indicated that some structural defects were present in the form of missing –NH groups presumably due to incomplete amidation or intramolecular cyclization of terminal amino groups. Characterization of PAMAMsilver nanocomposites by ultra-violet visible (UV-Vis) spectroscopy showed that the surface plasmon resonance (SPR) of colloidal silver shifted from approximately 414 nm to higher wavelengths suggesting specific interaction between PAMAM and silver nanoparticles. This is supported by the fluorescence spectra of generation 2.0 PAMAM-silver nanocomposite which exhibited quenching of the emission peaks of fluorophore at 510 nm after silver encapsulation. The particle sizes of colloidal silver at concentrations of 200 and 800 ppm were found between 5 and 20 nm as determined from transmission electron microscopy (TEM). In this study, it was demonstrated that low generation of PAMAM dendrimers able to act as template to pre-organize silver ions following in situ reduction with sodium borohydride (NaBH4). PAMAM dendrimer of generation 2.0 was screened for its potential antibacterial activity against two bacteria, viz, Escherichia coli ATCC 11229 (Gram negative) and Staphylococcus aureus ATCC 6538 (Gram positive) using disk diffusion technique (DDT) and minimum inhibition concentration (MIC) method. Study on the effect of ratios of silver concentration to PAMAM generation 2.0 indicated that the antibacterial activity against both Gram negative and Gram positive bacteria was lower than for PAMAM-silver nanocomposite. The findings also indicate that the presence of silver in the dendrimer has further enhanced the antibacterial activity against Gram negative bacteria which was also dependent on the concentration of silver solutions. The higher antibacterial activity of PAMAMsilver nanocomposite could be due to strong interaction between negatively charged bacterial cell wall and the cationic PAMAM dendrimer, which possibly decrease the distance between silver nanoparticles and the bacteria. This interaction then enables the silver nanoparticles easily attached to the bacterial cell surface and even penetrate the cell walls, killing the bacteria resulting in the antimicrobial activity.